Reduced foraging in the presence of predator cues by the Black Spiny-tailed Iguana, Ctenosaura similis (Sauria: Iguanidae) - Vincent R. Farallo; Mahmood Sasa; Dennis K. Wasko; Michael R. J. Forstner (Phyllomedusa: Journal of Herpetology, 2010)
The presence of a predator may have direct and indirect effects on the behavior of the prey. Although altered behavior may help prey avoid predators, it also can have a potential impact on critical activities such as foraging. Predator-prey interactions are routinely studied in laboratory-based experiments owing to theperceived difficulties of conducting such experiments in natural settings. We conducted an experimental study under field conditions in Palo Verde National Park in northwestern Costa Rica to assess behavioral responses of Black Spiny-tailed Iguanas (Ctenosaurasimilis) to the presence of predators and predator cues. Free-roaming iguanas were offered mango in designated areas in the presence of a predator (Boa constrictor), a predator cue (B. constrictor feces), and a control (no predator or predator cue). Results indicate that iguanas reduced their foraging efforts in the presence of both a predator and its cue.